Effects of Extract from Cole Pollen on Lipid Metabolism in Experimental Hyperlipidemic Rats - Yue Geng; Wen-li Tu; Jing-jing Zhang; Liang Zhang; Jian Zhang (The Scientific World Journal)
In order to evaluate the effects of extract by SCE (supercritical carbon dioxide extraction) from cole pollen on lipid metabolism in hyperlipidemic rats, the experimental hyperlipidemic rats were established by providing with high fat diets, and randomized into six groups. After four weeks of perfusion diets into stomach, the rats were executed, and lipid levels of serum and hepatic tissue were detected. The serum levels of TC and TG were significantly lower in the pollen extract groups and MC group than in HFC group. Hepatic TC levels were decreased in rats fed pollen extract and lovastatin compared with HFC group. A higher concentration of HDL-C and apoAI in hepatic tissue was measured after intake of the pollen extract compared to the HFC group (P<0.05). LCAT activity in serum of pollen extract groups was significantly higher than that in HFC group, and also HMG-CoA reductase showed decreasing tendency in pollen extract groups. The contents of DHA in pollen extract groups were found higher than those in HFC group. Cole pollen extract enriched in alpha-linolenic acid is likely to be a novel source of ALA which is probably responsible for favorable lipid changes through promoting transportation, excretion, and metabolism of cholesterol in hepatic tissue and serum.